Liraglutide in a real-world setting: Joint modeling of metabolic response, prediction of efficacy, and cardiovascular risk - Alonso-Troncoso, Isabel; Carollo-Limeres, Carmen; Rios-Prego, Mónica; Guler, Ipek; Cadarso-Suárez, Carmen; F-Mariño, Alexis (Endocrinologia, diabetes y nutricion, 2019)
The worldwide prevalence of type 2 diabetes mellitus increases in parallel to that of obesity. Liraglutide (LRG), a glucagon-like peptide-1 receptor agonist, can reduce body weight. This study assessed the metabolic efficacy of LRG in real-world clinical practice. An observational, retrospective cohort study including patients treated with LRG for at least one year (187 patients). Anthropometric and metabolic variables, a composite endpoint, factors predicting response to LRG, and cardiovascular risk over time were assessed. A linear mixed-effects model with a bivariate structure was constructed to investigate the time-dependent relationship between weight and HbA1c values. HbA1c levels and weight significantly decreased in the first 12 weeks, and the decrease persisted at 12 and 24 months in all subgroups studied. Mean weight and HbA1c decreases after 24 months were 8.5kg and 1.7% respectively. HbA1c values <7% were achieved by 42% of patients at 12 months and by 40% at 24 months. Treatment with LRG allowed for reduction in insulin dose. No serious adverse events were noted. Cardiovascular risk decreased from high to moderate-low. Under standard clinical practice conditions, LRG achieved a better metabolic response than seen in clinical trials. Efficacy at 12 weeks of treatment is a good predictor of response. LRG allows for delaying or reducing insulin dose by improving both weight and glucose control. Cardiovascular risk improved.